Exogenous glutathione reverses meropenem resistance in carbapenem-resistant Klebsiella pneumoniae - Yi, Juan; Liu, Chao; Yang, Ping; Wu, Zhen-chao; Du, Chun-jing; Shen, Ning (Frontiers in Pharmacology, 2023)
The rate of carbapenem-resistant Klebsiella pneumoniae (CRKP) infection has been increasing rapidly worldwide and, poses a significant risk to human health. Effective methods are urgently needed to address treatment failures related to antibiotic resistance. Recent research has reported that some drugs in combination with antibiotics have displayed synergistic killing of resistant bacteria. Here, we investigated whether glutathione (GSH) can synergize with meropenem, and enhance its effectiveness against CRKP.Synergistic activity was assessed by checkerboard and time-killing assays. The mechanism of these combinations was assessed by total ROS and membrane permeability assays. The bacterial metabolites were assessed by LC-MS/MS.The FICIs of GSH and meropenem were approximately 0.5 and the combined treatment with GSH and meropenem resulted in a more than 2log10 CFU/mL reduction in bacteria compared to the individual treatments. These findings indicated the synergistic effect of the two drugs. Moreover, the meropenem MIC of CRKP was reduced to less than 4 mg/L when combined with 6 mg/mL GSH, indicating that GSH could significantly reverse resistance to meropenem in bacteria. The production of ROS in bacteria was determined by flow cytometry. After adding GSH, the ROS in the GSH group and the combined group was significantly higher than that in the control and meropenem groups, but there was no significant difference between the combined and GSH groups. The metabolic disturbance caused by GSH alone and in combination with meropenem was significant intracellularly and extracellularly, especially in terms of glycerophospholipid metabolism, indicating that the synergistic effect of the combined use of GSH and meropenem was relevant to glycerophospholipid metabolism. In addition, we measured the cell membrane permeability. The cell membrane permeability of the combination group was significantly higher than that of the blank control or monotreatment groups. This confirmed that the GSH can serve as a meropenem enhancers by disturbing glycerophospholipid metabolism and increasing cell membrane permeability.GSH and meropenem display a synergistic effect, wherein GSH increases the sensitivity of CRKP to meropenem. The synergy and susceptibility effects are thought to related to the increased membrane permeability resulting from the perturbations in glycerophospholipid metabolism, presenting a novel avenue for CRKP treatment.